2022
DOI: 10.3390/microorganisms10112206
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiota and Tumor—A New Perspective of Tumor Pathogenesis

Abstract: Microorganisms have long been known to play key roles in the initiation and development of tumors. The oral microbiota and tumorigenesis have been linked in epidemiological research relating to molecular pathology. Notably, some bacteria can impact distal tumors by their gastrointestinal or blood-borne transmission under pathological circumstances. Certain bacteria drive tumorigenesis and progression through direct or indirect immune system actions. This review systemically discusses the recent advances in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 154 publications
0
5
0
Order By: Relevance
“…Oral microorganisms have the ability to colonize extra-oral organs, such as the lungs, colorectum, and stomach (Park et al, 2021). They employ their own virulence factors and metabolites to disrupt the epithelial barrier and extracellular matrix, induce an inflammatory microenvironment and immunosuppressive tumor microenvironment, thereby influencing both local and distant tumors (Li S. et al, 2022;Ma et al, 2023). The anaerobic conditions within the tumor microenvironment further facilitate the accumulation of anaerobic oral microorganisms in tumors (Wu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Oral microorganisms have the ability to colonize extra-oral organs, such as the lungs, colorectum, and stomach (Park et al, 2021). They employ their own virulence factors and metabolites to disrupt the epithelial barrier and extracellular matrix, induce an inflammatory microenvironment and immunosuppressive tumor microenvironment, thereby influencing both local and distant tumors (Li S. et al, 2022;Ma et al, 2023). The anaerobic conditions within the tumor microenvironment further facilitate the accumulation of anaerobic oral microorganisms in tumors (Wu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the dysbiosis of bacterial communities affects tumor development, mainly through chronic inflammation and immunosuppression, and certain oral microbiota and their metabolites have tumor‐promoting properties. On the other hand, specific tumor microenvironments also make great contributions to microbiota colonization (Li et al., 2022). Take F. nucleatum for instance, it was confirmed that its colonization to breast cancer is secondary to tumor initiation in mice experiments (Parhi et al., 2020).…”
Section: The Ways F Nucleatum Translocates To the Breast Tissue And C...mentioning
confidence: 99%
“…pathogens usually affect the mechanism of epithelial barrier function by the following mechanisms: (1) manipulating barrier-related genes or proteins to promote adhesion and internalization; (2) directly disrupting junctions and penetrating into underlying tissue. Moreover, the representative pathogens include F. nucleatum, T. forsythus, and Aggregatibacter actinomycetemcomitans(Abdulkareem et al, 2018;Li et al, 2022). The oral opportunistic pathogen, F. nucleatum, can bind and invade epithelial and endothelial cells through its virulence factors such as FadA, Fap2, and Fusobacterium outer membrane protein A, thus adhering to different sites.…”
mentioning
confidence: 99%
“…Simultaneously, the host’s immune system upholds a state of tolerance while curbing immune responses. This is achieved through the actions of mucosal dendritic cells and the release of anti-inflammatory cytokines like IL-10 and prostaglandin E2, the generation of T-regulatory cells also contributes to this process ( Li et al, 2022 ). Consequently, the oral mucosal tissues achieve a harmonious and well-organized stability, balancing the survival needs of various microorganisms ( Sami et al, 2020 ).…”
Section: Carcinogenic Mechanismmentioning
confidence: 99%